Renal impairment is not an independent adverse prognostic factor in patients with multiple myeloma treated upfront with novel agent-based regimens. - Eleftherakis-Papapiakovou, E.; Kastritis, E.; Roussou, M.; Gkotzamanidou, M.; Grapsa, I.; Psimenou, E.; Nikitas, N.; Terpos, E.; Dimopoulos, M.A. (Leukemia & lymphoma, 2011)
Abstract Renal impairment (RI) is a common presenting complication of multiple myeloma associated with significant morbidity and early mortality, while it has been associated with inferior survival in patients treated with conventional regimens. We assessed the impact of RI in 203 unselected consecutive patients treated upfront with novel agents (thalidomide, lenalidomide, bortezomib). RI was assessed by the estimated glomerular filtration rate (eGFR). RI (eGFR <60 mL/min) was present in 93 (45.8%) of patients at diagnosis and was associated with advanced age, advanced International Staging System (ISS) stage, poorer performance status, hypercalcemia, urine Bence-Jones proteinuria, anemia and thrombocytopenia. Myeloma response rates were similar for patients with or without RI. In univariate analysis RI was associated with shorter survival and a higher rate of early death (7% vs. 3.5%); however, when adjusted for other prognostic factors, RI was not independently associated with survival. In conclusion, in unselected newly diagnosed patients treated with novel agent-based therapies, RI is not independently associated with inferior survival, probably due to the significant activity of novel agents even in the context of RI.